Pengaruh Sales Growth, Total Asset Turnover, dan Operating Expense Ratio terhadap Kesulitan Keuangan dengan Profitabilitas sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Subsektor Industrial dan Basic Material yang Terdaftar di Bursa Efek Indonesia 2021 – 2024 - Adinda Adinda; Zufrizal Zufrizal; Muhammad Joni Barus (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study examines the effect of Sales Growth, Total Asset Turnover, and Operating Expense Ratio on financial distress, with profitability as a moderating variable, in industrial and basic material subsector companies listed on the Indonesia Stock Exchange from 2021 to 2024. Financial distress is measured using the Altman Z''-Score model, while profitability is proxied by Return on Asset. The sample comprises 308 observations from 77 companies selected through purposive sampling, analyzed using Moderated Regression Analysis (MRA) in SPSS. Results indicate that Total Asset Turnover has a positive and significant effect on financial distress, whereas Sales Growth and Operating Expense Ratio show no significant influence. Profitability fails to moderate the relationship between any of the three independent variables and financial distress, though it exerts a direct and significant effect on its own. The complete MRA model yields an Adjusted R Square of 0.206, meaning the independent variables explain 20.6 percent of the variation in financial distress, with the remaining variation attributable to factors outside the model. These findings are expected to assist company management in optimizing asset productivity as a strategy for preventing financial distress.